Bonding the foe – NETting neutrophils immobilize the pro-inflammatory monosodium urate crystals - Schorn, Christine; Janko, Christina; Krenn, Veit; Zhao, Yi; Munoz, Luis E.; Schett, Georg; Herrmann, Martin (Frontiers in Immunology, 2012)
In the presence of sodium, uric acid from purine metabolism precipitates as monosodium urate (MSU) needles and forms renal calculi or causes gouty arthritis in kidneys and joints, respectively. The latter is characterized by red, hot and swollen arthritic joints. Here we report the in vitro effect of MSU crystals on blood granulocytes and analyse their contribution to granuloma formation and neutrophil extracellular traps (NETs) formation (NETosis) in synovial fluid of patients with gouty arthritis in vivo. We observed that MSU crystals induce NETosis in vitro in a reactive oxygen species (ROS)-dependent manner. Indeed, blocking ROS (e.g. the oxidative burst) by various antioxidants partially inhibited NETosis induced by MSU crystals. Analyses of synovial fluids and of tissue sections of patients suffering from gout revealed that NETs are also formed in vivo, especially during acute gouty flares and/or granuloma formation. Since prolonged exposure to NETs carries the risk for the development of chronic inflammation we also studied the opsonisation of NETs, as a prerequisite for their clearance. The established dead cells’ opsonins C3b, galectin-9 and CRP decorated the residual dead cells` corpses and opsonized these for disposal. Surprisingly, all three soluble pattern recognizing molecules spared the spread NET structures. We conclude that (I) MSU crystals are strong inducers of ROS-dependent NETosis and (II) that the prolonged presence of NET-pathogen or NET-crystal aggregates observed in patients with systemic autoimmunity, especially in those with low serum DNase-1 activity, cannot be compensated by CRP, complement and galectin mediated phagocytic clearance.